2021
DOI: 10.1021/acsami.1c02643
|View full text |Cite
|
Sign up to set email alerts
|

Rapid In Situ Polymerization of Polyacrylonitrile/Graphene Oxide Nanocomposites as Precursors for High-Strength Carbon Nanofibers

Abstract: Graphene oxide (GO) has been widely used as an additive of polyacrylonitrile (PAN)-based carbon nanofibers (CNFs) to optimize its crystal structure and improve the mechanical performances of nanofibers. However, the homogeneous dispersion of GO nanosheets among entangled PAN molecular chains is always challenging, and the poor dispersion of GO severely limits its positive effects on both the structure and performances of CNFs. Considering this issue, this paper provides for the first time an effective solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 68 publications
2
36
0
Order By: Relevance
“…The FTIR spectra of polymer samples show the typical peaks of C�N bonds at 2240 cm −1 , C−H bonds at 2940, 1454, 1357, 1247, and 1070 cm −1 , and C�N bonds at 1620 cm −1 (Figure 3a). 7 In particular, the addition of OLC shifts the peak of C�N to lower wavenumbers (Figure 3b). It is inferred that the redshift of this peak is attributed to the interaction between C�N and OLC, which enlarges the conjugated electron system and results in the reduction of the vibration frequency of C�N bonds.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The FTIR spectra of polymer samples show the typical peaks of C�N bonds at 2240 cm −1 , C−H bonds at 2940, 1454, 1357, 1247, and 1070 cm −1 , and C�N bonds at 1620 cm −1 (Figure 3a). 7 In particular, the addition of OLC shifts the peak of C�N to lower wavenumbers (Figure 3b). It is inferred that the redshift of this peak is attributed to the interaction between C�N and OLC, which enlarges the conjugated electron system and results in the reduction of the vibration frequency of C�N bonds.…”
Section: Resultsmentioning
confidence: 96%
“…7 Moreover, the thickness of crystal domains (Lc) can also be evaluated from the XRD patterns, which is inversely proportional to the full width at half-maximum (fwhm) of the 17°p eak. 7 It is shown that the crystallinity of PAN keeps decreasing with the increasing addition of OLC, while the Lc of PAN increases as the addition of OLC rises from 0 to 1 wt %, and suddenly drops to a relatively low value with 5 wt % OLC (Figure 3f). It is deduced that the increased Lc mainly comes from the attraction of OLC to the PAN matrix (Figure 2e), which makes the polymer segments near the nanofillers stack up orderly to a larger thickness.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyacrylonitrile nanofibers and derived membranes with graphene and GO have been exploited for technical applications [74,75]. Poly(lactic acid), GO-based nanofibers and the resulting membranes have been employed in tissue engineering scaffolds [76].…”
Section: Polymer/graphene Nanofibers For Nanocomposite Membranesmentioning
confidence: 99%